Anticoagulation in COVID-19 patients – An updated systematic review and meta-analysis. Issue 219 (November 2022) - Reis, Stefanie; Popp, Maria; Schießer, Selina; Metzendorf, Maria-Inti; Kranke, Peter; Meybohm, Patrick; Weibel, Stephanie
Abstract: Background: Thromboembolic events are common complications of COVID-19. Clinical study results on safety and efficacy of anticoagulation in COVID-19 are controversial. Material and methods: This report updates our systematic review and random-effects meta-analysis on randomized controlled trials (RCTs) comparing standard prophylactic anticoagulation and intermediate or therapeutic anticoagulation in COVID-19 patients. We searched eligible studies for the update up to 4 February 2022 by weekly monitoring of RCTs in the Cochrane COVID-19 Study Register. Certainty of evidence was assessed using GRADE (Grading of Recommendations Assessment, Development and Evaluation). Results: For this update we included five new trials; a total of 13 RCTs with 7364 patients. Certainty of evidence was very low to low. We are uncertain whether low-dose prophylactic anticoagulation is favoured over placebo or no anticoagulation in the outpatient- or post-discharge-setting. In hospitalized patients with moderate and severe COVID-19, intermediate-dose anticoagulation may have little or no effect on thrombotic events or death (RR 1.03, 95 % CI 0.86–1.24), but may increase severe bleeding non-significantly (RR 1.48, 95 % CI 0.53–4.15). Therapeutic-dose anticoagulation may decrease thrombotic events or deaths in hospitalized patients with moderate COVID-19 (RR 0.64, 95 % CI 0.38–1.07; fixed-effect model RR 0.72, 95 % CI 0.57–0.91), but may have little or no effect in patients with severe disease (RR 0.98, 95 % CI 0.86–1.12). With therapeutic-dose anticoagulation, the risk of major bleeding may increase regardless of COVID-19 severity (RR 1.78, 95 % CI 1.15–2.74). Conclusions: Hospitalized, moderately ill COVID-19 patients may benefit from therapeutic-dose anticoagulation, while critically ill patients may not. Risk of major bleeding must be considered. Highlights: Thromboembolic events are common complications of COVID-19 Uncertainty remains regarding standard prophylactic low-dose anticoagulation in the outpatient- or post-discharge-setting Moderately ill COVID-19 patients may benefit from therapeutic-dose anticoagulation,  contrary to critically ill patients Therapeutic-dose anticoagulation may increase the rate of severe bleeding events